A Review on Oil Sardine II. Preservation by Canning, Curing and Smoking - Madhavan, P.; Nair, T. S. Unninkrishnan; Balachandran, K. K. (Fishery Technology, 1974)
The paper discusses three methods of preservation of oil sardine: canning, curing, and smoking. Commercial canning of sardines is relatively a new method in Indian with only minor interest from the firms until now. Curing finds importance as a method of preservation as it is the oldest known technique and also the cheapest method with only minimum investment. But the products are mostly poor quality with only limited storage life. Recently, smoked products have been gaining popularity among the consumers. Smoking is a process which is applicable to both lean and fatty fishes . Naturally, sardine can find a place among the smoked fish produced in our country.